2021
DOI: 10.2147/jaa.s304126
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and Patient Type 2 Innate Lymphoid Cells are Differently Affected by in vitro Culture Conditions

Abstract: Background Type 2 innate lymphoid cells (ILC2s) have emerged as key players in the development of type 2 driven diseases such as allergy and asthma. Due to their low number in the circulation, in vitro expansion is needed to unravel their mechanisms of action. Purpose The aim of this study is to assess the impact of different culture conditions and address whether the method of expansion may distinctly affect healthy donor or patient-derived ILC2s. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Approximatively 20–40% of lung ILC2 express PD-1, a proportion that is further increased upon influenza infection or papain challenge [ 162 ]. We, and others, have shown that IL-33 and γc cytokines also induce PD-1 expression [ 44 , 46 , 170 , 179 , 180 ]. PD-1 is mainly expressed by KLRG1 + ILC2 [ 170 ] and negatively regulates ILC2 proliferation and cytokine expression [ 44 , 46 , 124 , 163 , 170 , 178 , 179 , 181 , 214 ] ( Figure 2 ).…”
Section: Ilc Expression Of Ic—parallel With Adaptive Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximatively 20–40% of lung ILC2 express PD-1, a proportion that is further increased upon influenza infection or papain challenge [ 162 ]. We, and others, have shown that IL-33 and γc cytokines also induce PD-1 expression [ 44 , 46 , 170 , 179 , 180 ]. PD-1 is mainly expressed by KLRG1 + ILC2 [ 170 ] and negatively regulates ILC2 proliferation and cytokine expression [ 44 , 46 , 124 , 163 , 170 , 178 , 179 , 181 , 214 ] ( Figure 2 ).…”
Section: Ilc Expression Of Ic—parallel With Adaptive Immune Cellsmentioning
confidence: 99%
“…In accordance, ILC2 in bronchiolar alveolar lavage samples obtained after allergen challenge increased CD137 expression compared to blood ILC2 [ 190 ]. However, in another study, no changes in CD137 expression were found on in vitro stimulated ILC2 despite multiple culture conditions from both healthy donors or allergic patients [ 180 ]. While additional studies are warranted, evidence to date predominantly supports that tissue resident ILC2 may express CD137; yet the conditions of when and how CD137 is induced on ILC2, as well as how these impact various disease processes, remain unknown.…”
Section: Ilc Expression Of Ic—parallel With Adaptive Immune Cellsmentioning
confidence: 99%
“…Patients with EA exhibit worse symptoms than those with non‐EA (non‐eosinophilic asthma (NEA)), regardless of asthma severity 1 . Recent studies have confirmed the crucial involvement of innate lymphoid cells (ILC2s), a rare group of lymphocytes, in innate immune responses to allergic diseases 2 …”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies have confirmed the crucial involvement of innate lymphoid cells (ILC2s), a rare group of lymphocytes, in innate immune responses to allergic diseases. 2 Innate lymphoid cells lack antigen recognition receptors and produce IL-13 and IL-5, both of which are involved in EA pathogenesis. 3 Interleukin-33, which is produced by bronchial epithelial cells, is crucial for the activation of resident lung Th2 cells as well as ILC2s to produce IL-5, resulting in the development of chitin-induced airway eosinophilia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation